Biomass Mapping for an Improved Understanding of the Contribution of Cold-Water Coral Carbonate Mounds to C and N Cycling - Laurence Helene De Clippele (Frontiers Media S.A., 2021)
This study used a novel approach combining biological, environmental, and ecosystem function data of the Logachev cold-water coral carbonate mound province to predictively map coral framework (bio)mass. A more accurate representation and quantification of cold-water coral reef ecosystem functions such as Carbon and Nitrogen stock and turnover were given by accounting for the spatial heterogeneity. Our results indicate that 45% is covered by dead and only 3% by live coral framework. The remaining 51%, is covered by fine sediments. It is estimated that 75,034–93,534 tons (T) of live coral framework is present in the area, of which ∼10% (7,747–9,316 T) consists of Cinorg and ∼1% (411–1,061 T) of Corg. A much larger amount of 3,485,828–4,357,435 T (60:1 dead:live ratio) dead coral framework contained ∼11% (418,299–522,892 T) Cinorg and <1% (0–16 T) Corg. The nutrient turnover by dead coral framework is the largest, contributing 45–51% (2,596–3,626 T) C year–1 and 30–62% (290–1,989 T) N year–1 to the total turnover in the area. Live coral framework turns over 1,656–2,828 T C year–1 and 53–286 T N year–1. Sediments contribute between 1,216–1,512 T C year–1 and 629–919 T N year–1 to the area’s benthic organic matter mineralization. However, this amount is likely higher as sediments baffled by coral framework might play a much more critical role in reefs CN cycling than previously assumed. Our calculations showed that the area overturns 1–3.4 times the C compared to a soft-sediment area at a similar depth. With only 5–9% of the primary productivity reaching the corals via natural deposition, this study indicated that the supply of food largely depends on local hydrodynamical food supply mechanisms and the reefs ability to retain and recycle nutrients. Climate-induced changes in primary production, local hydrodynamical food supply and the dissolution of particle-baffling coral framework could have severe implications for the survival and functioning of cold-water coral reefs.